Zone Restrictions Orders in Canadian Courts and the Reproduction of Socio-Economic Inequality - Marie-Eve Sylvestre; Dominique Bernier; Celine Bellot (Oñati Socio-Legal Series)
While State and local governments have long turned to legal norms, such as vagrancy ordinances and anti-panhandling by-laws, and relied on displacement strategies ranging from orders to disperse and forced removals to control disorderly behavior in public spaces, the ways in which courts and legal actors working within the criminal justice system contribute to the monitoring of public spaces have almost completely gone unnoticed. This paper focuses on one court-imposed spatial tactic, namely zone restriction or "no go" orders. We suggest that despite the fact that these court orders rely on preventative discourses and pursue rehabilitative objectives, they may ultimately have punitive effects on the public poor and political demonstrators and contribute to creating and reproducing socio-economic inequality by creating obstacles for their reintegration, encouraging recidivism, putting the safety of individuals at risk and by neutralizing those who challenge the social and political order in various ways. Ultimately, these orders raise some concerns with respect to the rule of law since they are rarely challenged and generally appear to be shielded from review.